Successful Multimodality Management of Advanced Acinic Cell Carcinoma of The Parotid Gland: A Case Report - Christian O. Manginstar; Reinaldo Putra Hardian (CV. Inara, 2026)
Background Acinic cell carcinoma (ACC) is a rare malignant salivary gland tumor that predominantly arises in the parotid gland. Although generally considered a low-grade malignancy, locally advanced or recurrent disease presents significant therapeutic challenges because of its infiltrative behavior and the absence of standardized treatment strategies. Case Presentation: A 56-year-old man presented with a recurrent painful left submandibular mass three years after previous surgical excision. Magnetic resonance imaging demonstrated a large left parotid tumor with mandibular erosion. The patient underwent neoadjuvant transarterial chemoembolization (TACE), followed by wide tumor excision, radical neck dissection, and immediate deltopectoral flap reconstruction. Histopathological examination confirmed acinic cell carcinoma of the parotid gland with a pathological stage of ypT4aN0M0 (Stage IVA). The postoperative course was uneventful, with satisfactory wound healing and viable flap reconstruction. A second-stage flap division was successfully performed without complications. Conclusion: This case demonstrates that multimodality management incorporating neoadjuvant TACE, radical surgical resection, and reconstructive surgery can provide favorable short-term oncologic and functional outcomes in selected patients with advanced recurrent acinic cell carcinoma of the parotid gland. Multidisciplinary collaboration remains essential for individualized treatment planning in this rare malignancy.